Primary mediastinal hydatid cysts - Tolga Semerkant (Journal of Surgery and Medicine, 2020)
Hydatid cysts are a parasitic disease caused by Echinococcus granulosus, and 0.5 to 2.6% of all hydatid cysts are in the mediastinum. In this study, we presented primary mediastinal hydatid cysts. All patients underwent chest X-ray and thoracic computed tomography (CT), and only one patient underwent thoracic magnetic resonance imaging (MRI) due to the association with spinal cord. All lesions removed through thoracotomy were confirmed pathologically, and no postoperative complications were observed, except for one patient. Anthelmintic treatment was started in one patient with vertebral involvement. No recurrence was observed in any of the patients. Although mediastinal hydatid cysts are rarely encountered, it is difficult to differentiate mediastinal hydatid cysts from other mediastinal diseases. However, the diagnosis is often made intraoperatively. Despite being a benign disease, mediastinal hydatid cysts should be removed surgically, as they may lead to serious complications due to deformation.